Bioremediation of Hydrocarbon: A Mini Review (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
Several contaminants that are present in the environment are able to be removed through the physical and chemical approach. Environmental rehabilitation is a challenge especially in large water bodies like rivers due to the volume and fastmoving property of river water. The exorbitant cost, safety and efficiency of physicochemical methods are important issues especially to remediate dissolved compounds such as pesticides, drug, and heavy metals. Nowadays, environmental rehabilitation using biological approach or known as bioremediation gets great attention as the treatment processes are environmentally friendly, low cost and easy to handle. Moreover, the result is highly satisfactory and at the same time cause no harm to the environment. This mini-review highlights the application of bioremediation to clean contaminated environment. The advantages and disadvantages will also be discussed.
Keywords: Bioremediation, Pollution, Environment, Petroleum, hydrocarbon